ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS DALAM LAPORAN KEUANGAN PERUSAHAAN - Tri Wulandari; Hidayat Darwis (JURNAL AKUNTANSI, 2020)
The purpose of this study is to analyze the company's financial performance with a case study at PT. Marina Berto Tbk. The period 2012 to 2015. The research method used is a descriptive causality method, which describes the company's financial performance in terms of liquidity ratios, solvency ratios and profitability ratios compared to the average ratios of similar industry companies. The results showed that in general the financial performance of PT. Marina berto Tbk is below the industry average, which means it's not good. Although when viewed from the current ratio, quick ratio, total assets to debt ratio is still relatively safe to finance debt and operations, but due to a decline in profits in 2014 and 2015 because the company's cash ratio is below standard. And in terms of corporate profitability ratios that year experienced difficulties in generating profits because the company's concentration on increasing the quantity of production and development in manufacturing, then the financial performance was getting worse.